Pengetahuan dan Sikap Remaja Putri dengan Perilaku Memeriksa Payudara Sendiri (Sadari) di SMP Negeri 02 OKU Tahun 2018 - Berta Afriani (LPPM STIKES Al-Ma'arif Baturaja, 2018)
The background of this research is based on data from the WHO in 2030 will occur in Indonesia leap in value cancer seven times. Early detection is very important, from our preliminary step to determine at an early stage tumors or lumps in the breast so as to reduce the death rate due to the cancer disease. The purposes of this research is to know the relationship between the knowledge and gesture of teenage girls with the way to check their breast by them own self (SADARI) in Junior High School number 2 at Baturaja OKU, on 2015th. The writer used analytic survey method with cross sectional which the data related to the independent variable, that is the knowledge and gesture and the dependent variable is the way to check teenage girls’ breast by them own self (SADARI). The sample took by random sampling with a sample size was 148. The writer used bivariate analysis and univariate analysis to statistic test. In this research, the writer find there are 40 respondents (47,1%) of 85 respondents who aware behavioral and have a good knowledge, and there are 24 respondents (26,7%) of 90 respondents who aware behavioral and have a good gesture. From the statistic test result there is a significant value p = 0,021 by Chi-Square test, it means that there is a meaningful relation between the knowledge and gesture of teenage girls with the way to check their breast by them own self (SADARI). Meanwhile, there is a significant value p = 0,000 by Chi-Square test, it means that there is meaningful relation between the gesture of teenage girls and the way to check their breast by them own self (SADARI). The writer concludes that there is a meaningful relation between the knowledge and gesture of teenage girls with the way to check their breast by them own self (SADARI), and there is meaningful relation between the gesture of teenage girls and the way to check their breast by them own self (SADARI).